Ancient Divergence Driven by Geographic Isolation and Ecological Adaptation in Forest Dependent Sundaland Tree Squirrels - Hinckley, Arlo; Hawkins, Melissa T. R.; Achmadi, Anang S.; Maldonado, Jesús E.; Leonard, Jennifer A. (Frontiers in Ecology and Evolution, 2020)
A surprising amount of hidden phylogenetic diversity exists in the small to medium size, drab colored squirrels of the genus Sundasciurus. This genus is endemic to Sundaland and the Philippines, where it is widespread. An earlier revision of this genus found that the high elevation ‘populations’ of the widespread, lowland slender squirrel (S. tenuis) were different species. Previous phylogenies based on mitochondrial cytochrome b sequences also suggested that the widespread, lowland Low’s squirrel (S. lowii) and the narrow endemic Fraternal squirrel (S. fraterculus) are not reciprocally monophyletic. Additionally, deep divergences have been identified between lineages within Low’s squirrel that date to the early Pliocene. Here we focus on evaluating the relationships and differences within and between populations of these two nominal species using whole mitochondrial genome sequences, nuclear intron sequences, and morphology. We reassess the taxonomy of this group, revalidate the species status of Robinson’s squirrel (Sundasciurus robinsoni Bonhote, 1903), support the species level recognition of the Natuna squirrel (Sundasciurus natunensis Thomas, 1895) and identify three other lineages that require further study. We estimate times of divergence and integrate geologic history to find that most of the divergences are pre-Pleistocene, and thus predate the Pleistocene flooding of Sundaland. Biogeographic, and ecological factors may have played a more important role than climatic factors in generating these patterns. While divergence in allopatry seems to be the main process driving speciation in lowland Sundaland squirrels (Sundasciurus), ecomorphological and behavioural adaptations in this clade suggest an important role of niche divergence.